Paper-based analytical devices for environmental analysis. Issue 6 (22nd February 2016) - Meredith, Nathan A.; Quinn, Casey; Cate, David M.; Reilly, Thomas H.; Volckens, John; Henry, Charles S.
Abstract : The field of paper-based microfluidics has experienced rapid growth over the past decade, in particular with new applications to environmental analysis. Abstract : The field of paper-based microfluidics has experienced rapid growth over the past decade. Microfluidic paper-based analytical devices (μPADs), originally developed for point-of-care medical diagnostics in resource-limited settings, are now being applied in new areas, such as environmental analyses. Low-cost paper sensors show great promise for on-site environmental analysis; the theme of ongoing research complements existing instrumental techniques by providing high spatial and temporal resolution for environmental monitoring. This review highlights recent applications of μPADs for environmental analysis along with technical advances that may enable μPADs to be more widely implemented in field testing.